Seasonal selection and resource dynamics in a seasonally polyphenic butterfly. (29th November 2012) - Morehouse, N. I.; Mandon, N.; Christides, J.‐P.; Body, M.; Bimbard, G.; Casas, J.
Abstract Seasonal polyphenisms are widespread in nature, yet the selective pressures responsible for their evolution remain poorly understood. Previous work has largely focussed either on the developmental regulation of seasonal polyphenisms or putative 'top‐down' selective pressures such as predation that may have acted to drive phenotypic divergence. Much less is known about the influence of seasonal variation in resource availability or seasonal selection on optimal resource allocation. We studied seasonal variation in resource availability, uptake and allocation in Araschnia levana L., a butterfly species that exhibits a striking seasonal colour polyphenism consisting of predominantly orange 'spring form' adults and black‐and‐white 'summer form' adults. 'Spring form' individuals develop as larvae in the late summer, enter a pupal diapause in the fall and emerge in the spring, whereas 'summer form' individuals develop directly during the summer months. We find evidence for seasonal declines in host plant quality, and we identify similar reductions in resource uptake in late summer, 'spring form' larvae. Further, we report shifts in the body composition of diapausing 'spring form' pupae consistent with a physiological cost to overwintering. However, these differences do not translate into detectable differences in adult body composition. Instead, we find minor seasonal differences in adult body composition consistent with augmented flight capacity in 'summer form' adults. In comparison, we find much stronger signatures of sex‐specific selection on patterns of resource uptake and allocation. Our results indicate that resource dynamics in A. levana are shaped by seasonal fluctuations in host plant nutrition, climatic conditions and intraspecific interactions.